Interacting with tumor cells weakens the intrinsic clockwise chirality of endothelial cells - Hang, Benson; Jassem, Eman; Mohammed, Hanan; Wan, Leo Q.; Herschkowitz, Jason I.; Fan, Jie (APL bioengineering, 2022)
Endothelial cells (ECs) possess a strong intrinsic clockwise (CW, or rightward) chirality under normal conditions. Enervating this chirality of ECs significantly impairs the function of the endothelial barrier. Malignant tumor cells (TCs) undergo metastasis by playing upon the abnormal leakage of blood vessels. However, the impact of TCs on EC chirality is still poorly understood. Using a transwell model, we co-cultured the human umbilical vein endothelial cells or human lung microvascular endothelial cells and breast epithelial tumor cell lines to simulate the TC–EC interaction. Using a micropatterning method, we assessed the EC chirality changes induced by paracrine signaling of and physical contact with TCs. We found that the intrinsic clockwise chirality of ECs was significantly compromised by the TC's physical contact, while the paracrine signaling (i.e., without physical contact) of TCs causes minimal changes. In addition, ECs neighboring TCs tend to possess a left bias, while ECs spaced apart from TCs are more likely to preserve the intrinsic right bias. Finally, we found the chirality change of ECs could result from physical binding between CD44 and E-selectin, which activates protein kinase C alpha (PKCα) and induces pseudopodial movement of EC toward TC. Our findings together suggest the crucial role of EC–TC physical interaction in EC chirality and that weakening the EC chirality could potentially compromise the overall endothelial integrity which increases the probability of metastatic cancer spread.